Pemberdayaan Masyarakat Dalam Dukungan Suami Dengan Pemilihan Jenis Kontrasepsi Iud Pada Wanita Usia Subur di Kelurahan Ladang Bambu Kecamatan Medan Tuntungan - Suriati Lubis; Desi Anggraini (Journal of Community Development, 2021)
Intra-Uterine Devices are an effective, safe and convenient contraceptive option for many women Husband support in family planning is a tangible form of men's concern and responsibility. Husbands who are the head of the family must be wise in making decisions, both for themselves and for their family members including their wives. This community service aims to increase husband support with the selection of Intra uterine Device contraception in women of childbearing age. subjects in the community service activities were women of childbearing age in Mango Village, Ladang Bambu District, totaling 15 people. At the initial stage, an approach was made to the residents to deliver counseling material using the lecture method, the implementation of immunization assisted by the village midwife and continued with a question and answer session.Community service activities with the title "Community Empowerment in Increasing husband support with the selection of Intra Uterine Device contraceptive types in women of childbearing age in Mangga Village, Medan Tuntungan District, 2022" were carried out on Saturday, January 29, 2022 at 09.00 WIB until completion. At the time of the activity, residents who came to register, then heard counseling material about increasing husband support with the selection of Intra Uterine Device contraceptive types in women of childbearing age, data collection was carried out which was assisted by the village midwife. It is expected for health workers to conduct health counseling to women of childbearing age, and mothers know the benefits of the type of contraceptive Intra Uterine Device in women of childbearing age.